Generating Rainfall IDF Curves Using IMD Reduction Formula and Choosing the Best Distribution for Babylon City, Iraq - Sajad Khalil Al‐Jalili; Haider M. Zwain; Ali Mohsen Hayder (Engineering Reports)
ABSTRACT Intensity‐duration‐frequency (IDF) models are considered one of the most important tools used in water resources projects, as well as the design and planning of hydraulic structures such as sewerage channels, bridges, culverts, and road networks. This study aims to generate IDF curves for the Iraqi city of Babylon based on the Indian Meteorological Department (IMD) empirical reduction formula and to choose the optimal distribution that gives the greatest rainfall intensity among the three distributions used in this research (generalized extreme value, Log‐Pearson type III, and Gumbel). This study examined daily rainfall data collected from the Iraqi Authority of Meteorology and Seismic Monitoring for a period of 32 years, from 1991 to 2022. The IMD reduction formula was used to calculate rainfall intensity for shorter durations (5, 10, 20, 30, 60, 120, 360, 720, and 1440 min) and custom return periods (2, 5, 10, 25, 50, and 100 years). To determine the goodness of fit for the data distributions, the Easy Fit 5.6 program was applied with three tests (the χ2 test, the Anderson–Darling test, and the Kolmogorov–Smirnov test). The results showed that all distributions were acceptable for both tests and all storm durations and that the rainfall intensity decreased with increasing duration of the rainstorm. It also showed that rainfall increases rainfall intensity during large return periods. Based on the criteria of AIC and BIC, the LP‐3 distribution was chosen as the best distribution to simulate rainfall in Babylon City using the IDM reduction formula.